2013
DOI: 10.1177/1941738113502296
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Changes in Aging

Abstract: Muscle physiology in the aging athlete is complex. Sarcopenia, the age-related decrease in lean muscle mass, can alter activity level and affect quality of life. This review addresses the microscopic and macroscopic changes in muscle with age, recognizes contributing factors including nutrition and changes in hormone levels, and identifies potential pharmacologic agents in clinical trial that may aid in the battle of this complex, costly, and disabling problem.Level of Evidence: Level 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 40 publications
2
59
2
1
Order By: Relevance
“…Nucleation was also affected by the cytokine, since the number of nuclei per visible fiber was reduced from 9 to 5 for the concentration of 80 ng/mL ( Figure 3C). All these morphological changes were consistent with those related to sarcopenia induced by TNF-α 25,26,30,39,40 . In order to test whether functional changes were also compatible, we set the concentration of TNF-α to 40 ng/mL for the remaining experiments, since it was the concentration for which some effects could be observed without becoming too adverse.…”
Section: Resultssupporting
confidence: 85%
“…Nucleation was also affected by the cytokine, since the number of nuclei per visible fiber was reduced from 9 to 5 for the concentration of 80 ng/mL ( Figure 3C). All these morphological changes were consistent with those related to sarcopenia induced by TNF-α 25,26,30,39,40 . In order to test whether functional changes were also compatible, we set the concentration of TNF-α to 40 ng/mL for the remaining experiments, since it was the concentration for which some effects could be observed without becoming too adverse.…”
Section: Resultssupporting
confidence: 85%
“…84 With the aging process, other contributing factors include state of chronic inflammation, 85 functional and structural decline of the neuromuscular systems, lower muscle turnover and repair capacity due to decreased muscle protein synthesis, and altered endocrine function. [86][87][88][89][90] Our study showed that the positive association between sarcopenia with falls and fractures was independent of most of the applied sarcopenia definitions. However, using the EWGSOP and IWGS definitions, which include low physical performance and/or grip strength in addition to low muscle mass in their diagnostic algorithm, 24 higher risks of falls and fractures among sarcopenic individuals compared with nonsarcopenic individuals were shown.…”
Section: Discussionmentioning
confidence: 60%
“…With aging, various physiological changes occur, although muscle aging is prominent 1 . Age-related muscle loss can be characterized as decrease of muscle mass, motor unit, and muscle cross sectional area, and finally decrease of muscle quality 1, 2, 3. Muscle loss in particular can lead to a decrease of functional capacity of muscle and increase risk of developing age-related problems, such as chronic diseases 4 …”
Section: Introductionmentioning
confidence: 99%
“…With one of the muscle's important characteristics, plasticity, 3 muscle can adapt to environment throughout life, and trainability of skeletal muscle and muscle improvement has been demonstrated in aging 6 . Also, exercise accelerates production of various cytokines and growth factors or regulates homeostasis 5 .…”
Section: Introductionmentioning
confidence: 99%